COMMAND DIRECTIVE ILLOCUTIONARY ACT PERFORMED IN KINGSGLAIVE: FINAL FANTASY XV MOVIE - Muliadana, Dhiyo; Putu Devi Maharani; Komang Dian Pusita Candra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
In society, directive illocutionary is very important to establish good communication. Directive speech is used in giving commands, requests, and suggestions to make the hearer do something. This study entitled “Command Directive Illocutionary Performed in Kingsglaive: Final Fantasy XV Movie” It aims for finding out the command directive illocutionary acts and the context of situation of directive illocutionary acts utterance performed by the main characters and the secondary characters. This study also focusses on finding command illocutionary act that used imperative and declarative as their sentences. The command directive illocutionary acts are discussed using the theory of directive illocutionary acts proposed by Kreidler (1998: 189-190) and the context of situation is discussed using theory of the context of situation proposed by Halliday and Hasan (1985: 12). In collecting the data, the writer watched the movie and noted the utterances that contain command directive illocutionary acts in the movie script. The method used in analysing data was descriptive qualitative method. In presenting the findings, formal and informal methods are used. The formal method is used to show the percentage of sentence structure of command directive illocutionary acts using table and the informal method is used to explain the data descriptively through words. In this study, 21 data were found regarding illocutionary acts of directive command. The finding in the analysis also shows command uttarance that uttered by the characters in the film Kingsglaive: Final Fantasy XV used declarative sentences and imperative sentences in their uttarances.